Novel environment exposure drives temporally defined and region-specific chromatin accessibility and gene expression changes in the hippocampus - Lisa Traunmüller; Erin E. Duffy; Hanqing Liu; Stella Sanalidou; Sebastian Krüttner; Elena G. Assad; Senmiao Sun; Naeem S. Pajarillo; Nancy Niu; Eric C. Griffith; Michael E. Greenberg (Nature Communications)
Abstract Exposure to novel environments (NE) induces structural and functional changes in multiple brain areas, including the hippocampus, driven in part by changes in gene expression. However, the cell-type-specific transcriptional and chromatin responses to NE remain poorly understood. We employed single-nucleus multiomics and bulk RNA-seq of the hippocampal DG, CA3, and CA1 regions of male mice to profile gene expression and chromatin accessibility following NE exposure. We observed region-specific responses in excitatory neurons and diverse transcriptional changes in inhibitory and non-neuronal cells. NE-regulated genes were enriched for secreted factors, and their cell-type-specific receptor expression highlighted candidate signaling pathways involved in learning and memory. We identified thousands of cell-type-specific chromatin accessibility changes, with coordinated expression and accessibility patterns implicating FOS/AP-1 as a key regulator. These data provide a rich resource of chromatin accessibility and gene expression profiles across hippocampal cell types in response to NE, a physiological stimulus affecting learning and memory.